FRI0240 SIRT-1 Regulates TGF-β Induced Dermal Fibroblast Migration via Modulation of CYR61 Expression. (15th July 2016) - Jeong, W.; Park, E.-J.; Kwon, E.-J.; Cho, M.; Kim, J.
Abstract : Background: SIRT1 is a NAD-dependent protein deacetylase that participate in cellular regulation. The increased migration of fibroblast is important phenotype in fibroblast activation. The role of SIRT1 in cell migration remains controversial whether SIRT1 act as a activator or suppressor for cell migration. Objectives: The aim of this study was to establish the role of SIRT1 in human dermal fibroblast migration and explore a target of SIRT1 for dermal fibroblast migration. Methods: Levels of SIRT1 expression were analysed in human dermal fibroblast by RT-PCR and western blotting before and after stimulation with tumour gowth factor-β (TGF-β) and resveratol. Human dermal fibroblasts were transfected with active SIRT1 expression vectors or with siRNA targeting SIRT1 or were treated with nicotinamide. Cyr61 expression analysis was performed by western blotting to study the role of SIRT1 on cell migration. The wound healing assay was performed due to analyze migration of human dermal fibroblasts. Results: SIRT1 and Cyr61 was expressed in human dermal fibroblasts and the stimulation of TGF-β further induced expression levels of SIRT1 and Cyr61 (figure a ). Treatment of resveratol, SIRT1 agonist or overexpression of SIRT1 also promoted expression of SIRT1 and Cyr61 in human dermal fibroblasts, whereas inhibition of SIRT1 activity by nicotinamide or knock down of SIRT1 down-regulated Cyr61 basal level as well as TGF-β or resveratol-induced Cyr61expression. Blocking of ERK signaling by PD98509 reduced TGF-β or resveratol-induced Cyr61 expression. Resveratol increased migration and nicotinamide attenuated resveratol-induced migration of human dermal fibroblasts. Furthermore, SIRT1 overexpression promoted cell migration whereas blocking Cyr61 attenuated SIRT1-stimulated migration of human dermal fibroblasts (figure b and c ). Conclusions: We suggested a role of SIRT1 in human dermal fibroblast migration. SIRT1 increased cell migration by stimulated Cyr61 expression for their target through the ERK signaling. SIRT1-induced Cyr61 production is very important for human dermal fibroblasts migration. References: Wei J, Ghosh AK, Chu H, Fang F, Hinchcliff ME, Wang J et al. The Histone Deacetylase Sirtuin 1 Is Reduced in Systemic Sclerosis and Abrogates Fibrotic Responses by Targeting Transforming Growth Factor beta Signaling. Arthritis Rheumatol. 2015;67(5):1323–34. doi:10.1002/art.39061 Akgedik R, Akgedik S, Karamanli H, Uysal S, Bozkurt B, Ozol D et al. Effect of resveratrol on treatment of bleomycin-induced pulmonary fibrosis in rats. Inflammation. 2012;35(5):1732–41. doi:10.1007/s10753-012-9491–0. Katherine T., Andrew L. CCN1 Expression By Fibroblasts is Required for Bleomycin-Induced Skin Scleroderma. Rheumatology 2015;doi: 10.1093/rheumatology/kev090.003 Disclosure of Interest: None declared